2021
DOI: 10.3329/jujbs.v9i1-2.53703
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heavy metal contents in some commercial turmeric samples available at Dhaka, Bangladesh

Abstract: Nowadays, the use of spices and other herbs have extensively increased due to their medicinal values all over the world. However, the monitoring of heavy metal contamination in spices has also been increased in recent years. A study has been conducted to determine the concentration of eight heavy metals such as Lead (Pb), Cadmium (Cd), Chromium (Cr), Arsenic (As), Zinc (Zn), Iron (Fe), Copper (Cu) and Manganese (Mn) in mainly three different types of turmeric samples (Curcuma longa). The turmeric samples analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Turmeric, like other raw materials, can be contaminated with heavy metals that accumulate in the body, leading to long-term health effects. In a study by Rahman et al [171], samples were analyzed using atomic absorption spectroscopy (AAS). The concentration of most heavy metals was within the limits recommended by the World Health Organization (WHO) (6.0000 ppm), with the exception of lead (12.3469 ppm).…”
Section: Bioavailability Disadvantages and Hazards Of The Use Of Curc...mentioning
confidence: 99%
“…Turmeric, like other raw materials, can be contaminated with heavy metals that accumulate in the body, leading to long-term health effects. In a study by Rahman et al [171], samples were analyzed using atomic absorption spectroscopy (AAS). The concentration of most heavy metals was within the limits recommended by the World Health Organization (WHO) (6.0000 ppm), with the exception of lead (12.3469 ppm).…”
Section: Bioavailability Disadvantages and Hazards Of The Use Of Curc...mentioning
confidence: 99%
“…Rahman, M.A. et al found twice the amount above the acceptable value of lead in unbranded turmeric samples collected from Dhaka city using atomic absorption spectroscopy (17). Akter, S., et al found similar result using the Ion Beam Analysis Technique (18).…”
Section: Introductionmentioning
confidence: 99%